Toward a Single‐Dose Vaccination Strategy with Self‐Encapsulating PLGA Microspheres. Issue 12 (3rd April 2017) - Bailey, Brittany A.; Ochyl, Lukasz J.; Schwendeman, Steven P.; Moon, James J.
Abstract : Poly(lactic‐ co ‐glycolic acid) (PLGA) microspheres have been widely examined for vaccine applications due to their attractive features of biocompatibility, biodegradability, ability to be internalized by antigen‐presenting cells, and long‐term antigen release. However, one of the major challenges for PLGA particle vaccines is the potential for antigen instability and loss of antigenicity and immunogenicity. To address this challenge, we have developed a new method of "self‐healing" encapsulation in PLGA microspheres, where pre‐made PLGA microspheres are loaded with protein antigens under aqueous conditions with minimal impact on their antigenicity and immunogenicity. In this report, we show that mice immunized with self‐encapsulating PLGA microspheres in a prime‐boost regimen generated significantly enhanced antigen‐specific CD8α+ T cell and antibody responses, compared with mice immunized with free, soluble protein admixed with calcium phosphate gel, a widely used adjuvant. Furthermore, a single‐dose of microspheres designed for >40 day sustained antigen release elicited robust cellular and humoral immune responses as efficiently as the prime‐boost vaccinations with calcium phosphate gel. Overall, these results suggest excellent potential of our self‐encapsulating PLGA microspheres as a vaccine platform for multiple‐dose as well as single‐dose vaccinations. Abstract : A "self‐encapsulating" procedure is developed that maintains antigenicity and immunogenicity of protein antigens during the preparation of poly(lactic‐ co ‐glycolic acid) microspheres. A single‐dose immunization with microspheres designed for >40 day antigen release elicits robust cellular and humoral immune responses in mice as efficiently as the prime‐boost immunizations with a routinely used adjuvant, suggesting great vaccine potential for these "self‐encapsulating" particles.